Clip joint modeling - Ståhl, Sebastian (My University, 2017)
In the automotive industry many parts are connected with different types of clips. One of them is studied in this Master Thesis. The studied clip is of metal and used to connect plastic parts to each other in the interior of the cars. The aim is to find the mechanical properties of this clip joint at room temperature and 80 C and to implement in a simple connector element representing the clip joint. The properties in the clip connection are determined by use of a combination of component tests and simulations. The tests are performed by fastening one part in the clip connection and applying a displacement at the other part and measuring the force to get a force vs displacement relation. In the finite element simulations are the same loading case used. In the numerical simulations is also a sensitivity analysis performed to investigate what parameters affects the properties of the clip joint the most. The study gives linear stiffnesses perpendicular to the hole and around all axes. The frictional force when sliding along the hole occurs is determined. The forces needed to assemble and dis-assemble the clip joint are also determined. All these properties are determined both for room temperature and for 80 C. The determined properties are only valid until a specific displacement when the plastic parts come in contact. From the sensitivity study is concluded that the most important parameters are the hole size and thickness of the clip. The determined properties make it possible to include a more realistic behavior of the clip joint in simulations with clips. It is possible because the representation in the connector element still is simple but more realistic and prevents the number of degrees of freedom to increase drastically. Keywords: Clip joint, Clip connection, Finite element simulation, Connector element, Parameter study, Friction, Stiffness, Temperature loading, Displacement test
Keywords: Teknisk mekanik; Produktion; Transport; Applied Mechanics; Production; Transport